2011
DOI: 10.1007/s00296-011-1973-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the classical, alternative, and mannose binding lectin pathway of the complement system in the pathogenesis of oligoarticular juvenile idiopathic arthritis

Abstract: The complement system plays a role in the pathogenesis of some autoimmunopathies. This longitudinal study evaluates the contribution of the complement system in the pathogenesis of oligoarticular juvenile idiopathic arthritis (JIA). Serum of the peripheral blood and the synovial fluid were investigated for the activity of the classical (CP), the mannose binding lectin (MBL), and the alternative pathway (AP). A total of 12 samples from peripheral blood (PB) and two samples from synovial fluid (SF) of girls with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
(13 reference statements)
1
7
0
1
Order By: Relevance
“…The remnant C for each pathway was determined using Wieslab Complement System Screenkits (Euro-diagnostica, Malmo, Sweden) essentially as described previously [7], [15], [16]. The kits are supplied pre-coated with specific activators for the CP, LP and AP.…”
Section: Methodsmentioning
confidence: 99%
“…The remnant C for each pathway was determined using Wieslab Complement System Screenkits (Euro-diagnostica, Malmo, Sweden) essentially as described previously [7], [15], [16]. The kits are supplied pre-coated with specific activators for the CP, LP and AP.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that overactivity or deficiency of some complement factors may facilitate JIA progression 9 , 10 , 11 , 12 . Those specific for lectin pathway activation have not been studied extensively.…”
mentioning
confidence: 99%
“…8 It has been suggested that overactivity or deficiency of some complement factors may facilitate JIA progression. [9][10][11][12] Those specific for lectin pathway activation have not been studied extensively. Mannose-binding lectin (MBL), ficolins and MBL-associated serine proteases (MASPs) have been detected in SF from patients suffering from rheumatoid arthritis and osteoarthritis.…”
mentioning
confidence: 99%
“…The enzyme immunoassay (EIA) method is proposed to estimate the whole three complement activation pathways (Brunner et al, 2012;Seelen et al, 2005;Thiel, Møller-Kristensen, Jensen, & Jensenius, 2002). The principle is shown in Fig.…”
Section: Enzyme Immunoassaymentioning
confidence: 99%